2006
DOI: 10.1007/s00362-006-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

A group sequential test for the inverse Gaussian mean

Abstract: Inverse Gaussian distribution, Sequential test, Group sequential test,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Table 3 gives the maximum sample sizes and the expected sample sizes for the fixed sample, the sequential probability ratio, and the group sequential test. Other examples can be presented that have the same general principle with different choices of α,β,µ 0 ,µ 1 and κ. Pocock [15] compared those tests for the mean of the normal distribution and showed that GST is more advantageous than the fixed sample test and SPRT in terms of sample size; in addition , Bacanlı & Demirhan [1] proposed the group sequential test for the mean of the inverse Gaussian distribution, in a similar way and showed that this test is more advantageous than the others.…”
Section: Group Sequential Test For the Mean Direction Of The Von Misementioning
confidence: 99%
“…Table 3 gives the maximum sample sizes and the expected sample sizes for the fixed sample, the sequential probability ratio, and the group sequential test. Other examples can be presented that have the same general principle with different choices of α,β,µ 0 ,µ 1 and κ. Pocock [15] compared those tests for the mean of the normal distribution and showed that GST is more advantageous than the fixed sample test and SPRT in terms of sample size; in addition , Bacanlı & Demirhan [1] proposed the group sequential test for the mean of the inverse Gaussian distribution, in a similar way and showed that this test is more advantageous than the others.…”
Section: Group Sequential Test For the Mean Direction Of The Von Misementioning
confidence: 99%
“…Group sequential tests can also be used in an experiment with only one treatment in which the response results are compared with a known standard. For a normal response with a known variance and 𝐻 0 hypothesis mean 𝜇 0 , the critical values 𝑍 𝑘 and Δ become √𝑛(𝜇 1 −𝜇 0 )/𝜎 [17,22]. When 𝐾 = 1, that is, for fixed sample size test, (17) becomes the classical hypothesis test for normal response.…”
Section: Advances In Fuzzy Systemsmentioning
confidence: 99%
“…Here, our aim is to compare the mean vectors of two continuous time multidimensional Gaussian processes (see, e.g., Akahira 2002;Bacanli and Demirhan 2008;Salau 2003) based on the observation of both paths with nuisance parameters in the covariances. There currently exist quite many continuous multivariate processes in Economy, Physics, or Medicine (among others) which follow Gaussian processes in continuous time.…”
Section: Introductionmentioning
confidence: 99%